Community Empowerment in Processing Snake Fruit into 'Salak Pie' Products as an Effort to Downstream the Commodity and Potential Alternative for Supplementary Feeding to Prevent Stunting in Sumberurip Village - Jauhani, Muhammad Afiful; Putri, Echa Amalia; Asti Purnomo, Faisal Kevin; Aida, Firzanah Bilqis; Ariefianto Putri, Hellen Maretha; Putri, Icha Fahrriza; Wahyuningtyas, Ika Putri; Pramestinasari, Intan; Azizah, Lailatul Nur; Priskila Haryuningtyas Ngantung; Rizaldy Andy Wijaya; Suhartatin; Zakiyah Maulidatul Hasanah (Jurnal Inovasi Sains dan Teknologi untuk Masyarakat, 2024)
Sumberurip Village, located in Pronojiwo District, Lumajang Regency, is predominantly an agricultural village where most of the community members farm salak (snake fruit). Up until now, the agricultural yield has primarily been marketed as raw produce. Additionally, stunting remains a critical issue in Lumajang Regency. Common challenges include highly fluctuating prices for salak, which tend to drop during harvest season due to an abundant supply, as well as the community’s limited knowledge and skills in processing and managing the fruit beyond raw sales. The Community Service Program for Village Development (KKN-UMD) of Jember University, Group 290, held in July - August 2024, aims to empower the Sumberurip community by increasing the value of salak through the creation of Salak Pie, which could also serve as an alternative snack for supplementary feeding programs (PMT) to help prevent stunting. The activities are conducted by providing training to the community on how to process salak into salak pie, as well as strategies for promoting and marketing these products. The Village Government and the community have warmly welcomed this initiative, considering it highly beneficial for enhancing the market value of their salak harvests and offering a nutritious local food alternative. The purpose of this community service is to equip the people of Sumberurip Village with knowledge and skills to process salak into Salak Pie, which is intended to boost the local economy while also providing a nutritious alternative for supplementary feeding programs.